Enhancing technical proficiency through small-sided basketball games: A strategic approach for students athletes - Perdima, Feby Elra; Apriansyah, Dolly; Sumantri, Ajis; Ertanto, Dody; Sofyan, Davi (UIR Press, 2024)
Background Problems: Due to the intricate nature of the game and the requirement for proficiency in core skills like dribbling, passing, shooting, and defensive positioning, basketball players frequently have difficulties developing their technical abilities. Traditional training approaches may not focus enough on these skills, leaving room for growth. Research Objective: This study investigates how well basketball players' technical skills may be improved through game-based instruction, particularly small-sided basketball games. The study aims to address the need for a more focused approach to technical elements by highlighting the value of focused practice in pertinent game scenarios. Methods: The type of research used was quantitative research with a sample of 12 amateur athletes. The instrument used is the game performance evaluation tool (GPET). Quantitative data from pre- and post-assessments were examined using the appropriate statistical techniques, such as paired t-tests or analysis of variance (ANOVA). For the study, basketball players with various skill levels were listed. Small groups of participants received specialised training to develop their technical abilities. Findings and Results: Participants' technical proficiency significantly improved after strategically focused practice using small-sided basketball games. The outcomes show that this game-based method works well for improving basic abilities, including passing, dribbling, shooting, and positioning defensively. The results highlight how effective it is to use small-sided games to help basketball players enhance their skills. Conclusion: The study concludes that small-sided basketball games are an effective strategy for improving basketball players' technical proficiency. Notwithstanding several constraints, such as a comparatively limited sample size and consistency in participant skill levels, the findings indicate that focused practice in pertinent gaming environments produces notable enhancements. To better understand the potential of this strategy for players of different skill levels, future studies should include additional variables like training amounts and differences in small-sided game structures.